Prevalence and seasonal distribution of viral etiology of respiratory tract infections in inpatients and outpatients of the pediatric population: 10 year follow-up - Kübra Aykaç; Ateş Kara; Ali Bülent Cengiz; Alpaslan Alp; Yasemin Özsürekci; Mustafa Şenol Akın; Sevgen Tanır-Başaranoğlu; Cihangül Bayhan; Eda Karadağ-Öncel; Mehmet Ceyhan (The Turkish Journal of Pediatrics)
The aim of this study was to investigate the prevalence and seasonal distribution of respiratory viruses in pediatric patients. Nasopharyngeal swab specimens, demographic and clinical information were collected from 1240 pediatric patients aged < 18 years between 2006 and 2015 in Hacettepe University Children`s Hospital. Multiplex RT-PCR (multiplex reverse transcriptase polymerase chain reaction) was performed to detect viral pathogens. A total of 1240 pediatric outpatients and inpatients who had been admitted to the hospital with symptoms of upper and lower respiratory tract infections (RTIs) were enrolled. Viruses were identified in 339 (27.3%) of cases, with the leading three viruses being respiratory syncytial virus (RSV, 74/339; 21.8%), human rhinovirus (62/339; 18.3%), and multiple viruses (56/339; 16.5%). Most of the patients were diagnosed with lower RTI (264/339; 77.8%) and antibiotics were administered to three quarters of positive patients (254/339; 74.9%). With an overall viral agent detection rate of 27.3%, the findings of the present study suggest that other respiratory pathogens, whether viral or bacterial, may also lead to hospital visits due to respiratory tract symptoms in children.